Controller placement mechanism in software defined network using k-median algorithm - Fahad, Noor Saad (2016)
Software Defined Network (SDN) decouples the control plane and the data plane, and moves the control plane to an external entity. The decoupling raises many challenges, and one of these is the placement of the controller in the network. This study aims to address controller placement problem in SDN. k-median is used to determine the placement of the controllers, and the placement with the lowest value of average propagation latency will be chosen. The placement compares two resulted placements. First, comparing to greedy algorithm that computes the combinations according to the order of the nodes and calculates the best values at each step, and the results were identical. The second comparison was with the combinations results from considering the placement from specific nodes, and the results showed that it gives higher results than depending on the lowest values resulted from the k-median. Finally, three controllers are chosen as the minimum number of controllers, they were evaluated in terms of delay and load, and as results it was found that three controllers are suitable number of controllers as long as there is no delay or load in the network. Combining the two algorithms for finding the placement and the number results in Controller Placement Mechanism (CPM)